Increase in joint stability at the expense of energy efficiency correlates with force variability during a fatiguing task. Issue 4 (26th February 2015) - Cashaback, Joshua G.A.; Cluff, Tyler
Abstract Empirical evidence suggests that our nervous system considers many objectives when performing various tasks. With the progression of fatigue, researchers have noted increase in both joint moment variability and muscular cocontraction during isometric force production tasks. Muscular cocontraction increases joint stability, but is metabolically costly. Thus, our nervous system must select a compromise between joint stability and energy efficiency. Interestingly, the continuous increase in cocontraction with fatigue suggests there may be a shift in the relative weighting of these objectives. Here we test the notion of dynamic objective weightings. Using multi-objective optimization, we found a shift in objective weighting that favoured joint stability at the expense of energy efficiency during fatigue. This shift was highly correlated with muscular cocontraction (R2=0.78, p<0.001) and elbow moment variability in the time (R2=0.56, p<0.01) and frequency (R2=0.57, p<0.01) domains. By considering a dynamic objective weighting we obtained strong correlations with predicted and collected muscle activity (R2=0.94, p<0.001).